The Capitalist Degree of Immortality - Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2021)
This note offers some speculative ideas worth considering. One of the key features of all hierarchical civilizations is their rulers' fear of death. This fear was famously narrated in the ancient myth of Gilgamesh – the Sumerian king who realized that, like all other humans, he too was destined to die and embarked on a desperate quest to annul his mortality . According to Lewis Mumford, this quest for immortality is the main reason why society's rulers are forever obsessed with building and fortifying power hierarchies – or 'megamachines', as he called them. Controlling these megamachines, Mumford argued, is the rulers' way of playing God, a futile yet all-possessive effort to conquer the future and live forever. In capitalism, the rulers finally figured out how to do it – sort of.
Keywords: P16; G01; G00; 330; capital; capitalization; future; immortality; power